College Drinking, Greek Affiliation And The Need To Fit In: An Analysis Of Social Norms And Motivations Associated With Fraternity and Sorority Binge Drinking - Dufrene, Chantel (2006)
This study proposes that members of Greek social organizations have higher rates of binge drinking as compared to other college students due to their greater acceptance of norms and motives that support binge drinking. The College Alcohol Study, a survey conducted by the Harvard School of Public Heath, was administered to 10, 904 university students. The survey measured various aspects of students' experiences at their respective universities including experiences with and perceptions of alcohol use. Logistic regression analysis was used to determine normative and motivational predictors of binge drinking for Greek and non-Greek students. The results show that Greek members binge drink at higher levels than do other students. The results also indicate that social norm and motive variables, which were thought to be predictive of binge drinking practices for all students, are better predictors of binge drinking for non-Greek members. Implications of theses findings, discussion of results, limitations of the study, and recommendations for future research are presented